Effect of Strain and Finisher Diet Non-Phytate Phosphorus Level on Performance and Litter Composition in Large Tom Production - Evans, A.M.; Swiger, B.N.; Blemings, K.P.; Lilburn, M.S.; Moritz , J.S. (International Journal of Poultry Science, 2014)
Sustainable practices relative to manure nutrient content are essential to commercial turkey production due to the perception that land application of poultry manure is a primary contributor to watershed eutrophication. The objective of our research was to determine the effect of finisher diet non-phytate phosphorus (nPP) levels on large tom performance and litter composition. Two experiments of similar concept were conducted and each experiment was a 2x2 factorial arrangement of treatments utilizing two commercial strains and two levels of dietary nPP (normal and low). In Experiment 1, dietary nPP was reduced during the last finisher diet [Normal (0.37) and Low (0.31)]. In Experiment 2, dietary nPP was reduced in the last 2 finisher diets [Normal (0.58) and Low (0.55) in the Finisher 1 diet and Normal (0.40) and Low (0.38) in the Finisher 2 diet]. Performance measurements were recorded from d 1-136 and d 1-126 in Exp 1 and 2, respectively and litter phosphorus (P) levels were determined. In Exp 1, both strains had similar ending weight (EW) and Strain B had an improved feed conversion ratio (FCR). There were no differences in performance or litter P due to nPP level, indicating the potential to decrease feed cost but not environmental impact. In Exp 2, Strain A had greater EW but increased FCR compared to Strain B. Regression equations that standardized strain EW predicted a decreased time of production and FCR for Strain A. The lower nPP level applied in both finisher diets decreased total litter P (p